Synthesis and Characterization of Bagasse (Saccharumofficinarum L.) Silica Gel Modified Diphenylcarbazone - Rismawaty Sikanna; Dwi Nur Assyifah Rajmah; Kurnia Ramadani; Musafira Musafira; Arfiani Nur; Amalyah Febryanti (Elkawnie: Journal of Islamic Science and Technology, 2021)
Abstract: Bagasse is a solid waste from the sugar cane milling process in the sugar industry. The waste can be used as an ingredient in making silica gel which functions as an adsorbent. This can be done by changing its chemical structure composition to increase its role and function. This study aims to determine the characteristics of silica gel synthesized from bagasse (Saccharumofficinarum L.) and modified using diphenylcarbazone as much as 0.24 g with sol-gel technique. The characterization results obtained from Fourier transform infrared (FTIR) analysis of diphenylcarbazone modified silica gel, namely the absorption of Si-OH, Si-O-Si groups supported by the appearance of C꞊O, C꞊N, NH, and N꞊N groups. Characterization using x-ray diffraction (XRD) showed a change in amorphous silica to crystals, with the results obtained showing a crystal size of 41.468 nm.Abstrak: Ampas tebu merupakan limbah padat yang berasal dari proses penggilingan tebu pada produksi gula. Limbah tersebut dapat dimanfaatkan sebagai bahan pembuatan silika gel yang berfungsi sebagai adsorben. Hal tersebut dapat dilakukan dengan mengubah komposisi struktur kimianya agar dapat meningkatkan peran dan fungsinya. Penelitian ini bertujuan untuk mengetahui karakteristik silika gel yang disintesis dari ampas tebu (Saccharumofficinarum L.) dan dimodifikasi menggunakan difenilkarbazon sebanyak 0,24 gr dengan teknik sol-gel. Diperoleh hasil karakterisasi dari analisis fourier transform infrared (FTIR) terhadap silika gel termodifikasi difenilkarbazon menunjukkan adanya serapan gugus Si-OH, Si-O-Si yang didukung dengan pembentukan gugus C꞊O, C꞊N, N-H, dan N꞊N. Karakterisasi menggunakan difraksi sinar-x (XRD) menunjukkan perubahan silika amorf menjadi kristal dengan hasil yang diperoleh memperlihatkan ukuran kristal sebesar 41,468 nm.